Determinants of the Match between Student Ability and College Quality - Dillon, Eleanor Wiske; Smith, Jeffrey Andrew (Journal of Labor Economics, 2017)
We examine how students of varying abilities sort (and are sorted) into colleges of varying qualities. Our data indicate substantial amounts of both academic undermatch (high-ability students at low-quality colleges) and academic overmatch (low-ability students at high-quality colleges). Student application and enrollment decisions, rather than college admission decisions, drive most deviations from academic assortative matching. Financial constraints, information, and the public college options facing students all affect this sorting, but mainly via college quality rather than the match between ability and quality. More informed students attend higher-quality colleges, even when doing so involves overmatching.